Analisis Yuridis Standar Operasional Prosedur Brigade Mobil (Brimob) dalam Penanganan Kriminalitas - Adhi Pradana Dwi Nugroho; Subhan Zein Sgn (FOCUS, 2026)
The Mobile Brigade (Brimob) of the Indonesian National Police plays a crucial role in maintaining public order and handling high-intensity security disturbances. The regulations on Standard Operating Procedures (SOP) for Brimob serve as the main guidelines for task execution; however, in its implementation, challenges are often encountered. This study aims to analyze the regulations and implementation of SOP for Brimob in handling criminality, as well as evaluate the alignment between existing legal theory and practical application in the field. A normative juridical approach was employed, with data gathered from relevant legislation and legal literature. The findings indicate that although SOP for Brimob is well-detailed in the law, gaps remain in its implementation, particularly concerning discretion and crowd control. Actions taken in emergency situations often risk violating the principles of proportionality and human rights. Therefore, revisions to the existing regulations are necessary to clarify SOP application and ensure legal certainty and protection of individual rights in every action taken by Brimob. This study also recommends enhancing training and supervision in the implementation of Brimob SOP in the field.